Effect of summer drought in 1999 on turf grass species. - Żurek, Grzegorz (Plant Breeding and Seed Science, 2000)
Basing on the response to drought in 1999 of 27 turfgrass cultivars and ecotypes of 9 species made possible ranking of turf grasses in the decreasing order of drought resistance.